Forest Carbon Stocks, Stock Changes and Implication to Forest Management in India - Jakati, R. D. (Indian Forester, 2016)
Forest management hitherto focussed attention on increasing the woody biomass and conserve biodiversity. However, in the light of climate change and the international negotiations the forest management needs to be reoriented to enhance the carbon stocks of the ecosystem and also conserve the biodiversity. The inter-relationship of the carbon stock in different pools, their changes with respect to different management treatments under different climate conditions throws open a vast field for research to understand carbon dynamics of the forest ecosystem. Preliminary analysis of the total carbon stock per hectare of different forest types in different canopy densities indicate that the carbon stock change is different for different forest type. The study of this may have practical forest management significance which is indicated here.